PRICAI 2016 : trends in artificial intelligence : 14th Pacific Rim International Conference on Artificial Intelligence, Phuket, Thailand, August 22-26, 2016, Proceedings /: trends in artificial intelligence : 14th Pacific Rim International Conference on Artificial Intelligence, Phuket, Thailand, August 22-26, 2016, Proceedings. (2016) - Unknown
No abstract available